RELATIONSHIP OF MOTIVATION AND WORK TRAINING TO INCENTIVES - Delavega, Lydia; Tampubolon, Emma (Universitas Kristen Indonesia, 2018)
Human resource is an importan factor for the achievement of organizational goals and company. Motivation and job training provided by the company is expected to improve employee incentive. The data obtained from the result of the research through the distribution of the questionnaire.The methodology that was used is a method of surveying descriptive were selected from having the character of 47 employees and data in statistically test. ( 1 ) motivation and job training own a combined the influence of a significant impact on the distribution of an incentive.It is obtained in test F with the results of the value of f count with a value of as much as 2.950 f count 2.950 > f tabel 3.21 and value of significant ,000< 0.05 percentage point then hypothesis ho were rejected and ha accepted, which means there are significant impact motivation and job training to the distribution of an incentive employees RS.Masmitra. (2) Motivation not too having influence who significance to the distribution of an incentive employees at RS.Masmitra.This having been demonstrated to t count ,799 < 2.014 Which means variable motivation in full not too had an influence on the distribution of an incentive employees.( 3 ) job training to have an influence and significant an employee at RS.Masmitra against the distribution of an incentive to t count 2.257 2.2014 so that ho were rejected and ha received. This was supported with a statement of respondents of job training that employees they really helped in diffusing if this is set to work training. The incentives in the firm make employee semangkin, got a big boost in finish the job but in the effect on incentives, of the study conducted in monitoring that motivation not too having the effect on incentives.It can be concluded that employees more feel job training factors had more influence against incentives.Keyword : Motivation, economic.